Balancing Livestock Needs and Soil Conservation: Assessment of Opportunities in Intensifying Cereal-Legume-Livestock Systems in West Africa - Abdoulaye, Tahirou (International Institute of Tropical Agriculture, 2009)
Presentation by T. Abdoulaye (IITA) to the CGIAR Systemwide Livestock Programme Livestock Policy Group Meeting, 1 December 2009